Toxic elements in arctic and sub-arctic brown bears: Blood concentrations of As, Cd, Hg and Pb in relation to diet, age, and human footprint - Boris Fuchs; Kyle Joly; Grant V. Hilderbrand; Alina L. Evans; Ilia Rodushkin; Lindsey S. Mangipane; Buck A. Mangipane; David D. Gustine; Andreas Zedrosser; Ludovick Brown; Jon M. Arnemo (Environmental Research, 2023)

Splitting hairs: dietary niche breadth modelling using stable isotope analysis of a sequentially grown tissue - Matthew C. Rogers; Grant V. Hilderbrand; David D. Gustine; Kyle Joly; William B. Leacock; Buck A. Mangipane; Jeffrey M. Welker (Isotopes in Environmental and Health Studies, 2020)

Dietary plasticity and the importance of salmon to brown bear (Ursus arctos) body size and condition in a low Arctic ecosystem - Lindsey S. Mangipane; Diana J. R. Lafferty; Kyle Joly; Mathew S. Sorum; Matthew D. Cameron; Jerrold L. Belant; Grant V. Hilderbrand; David D. Gustine (Polar Biology, 2020)
Ecological flexibility within animal populations can allow for variation in resource use and foraging decisions. We estimated brown bear ( Ursus arctos ) diet composition in Gates of the Arctic National Park and Preserve, Alaska from 2013 to 2015 to evaluate how variation in foraging behavior influences body condition and size. We used stable carbon (δ 13 C) and nitrogen (δ 15 N) isotope analyses of sectioned brown bear hair samples to evaluate assimilated diet. We then developed a set of a priori linear models to evaluate differences in the diet composition of brown bears ( n = 80) in relation to body fat (%) and mass. The proportion of meat (salmon [ Oncorhynchus keta ] and terrestrial meat combined) in the diet from July through late September varied between male and female bears, with males ( $$\stackrel{-}{x}$$ x - = 62%, SD = 30) assimilating significantly more meat than females ( $$\stackrel{-}{x}$$ x - = 40%, SD = 29). Most of the meat consumed came from marine-derived resources for males (53% of the total diet or 86% of the meat) and females (31% of the total diet or 77% of the meat). As we found the range of observed diets was unrelated to physiological outcomes (i.e., percentage body fat), we suggest that ecological flexibility within populations may provide an adaptive advantage by allowing individuals to reduce competition with conspecifics by foraging on alternate food resources. Identifying variable foraging behaviors within a population can allow for a better understanding of complex behaviors and, ultimately, lead to more informed management decisions related to habitat use, development, and harvest.

Plasticity in elk migration timing is a response to changing environmental conditions - Gregory J. M. Rickbeil; Jerod A. Merkle; Greg Anderson; M. Paul Atwood; Jon P. Beckmann; Eric K. Cole; Alyson B. Courtemanch; Sarah Dewey; David D. Gustine; Matthew J. Kauffman; Douglas E. McWhirter; Tony Mong; et al. (Global Change Biology, 2019)
Migration is an effective behavioral strategy for prolonging access to seasonal resources and may be a resilient strategy for ungulates experiencing changing climatic conditions. In the Greater Yellowstone Ecosystem ( GYE ), elk are the primary ungulate, with approximately 20,000 individuals migrating to exploit seasonal gradients in forage while also avoiding energetically costly snow conditions. How climate‐induced changes in plant phenology and snow accumulation are influencing elk migration timing is unknown. We present the most complete record of elk migration across the GYE , spanning 9 herds and 414 individuals from 2001 to 2017, to evaluate the drivers of migration timing and test for temporal shifts. The timing of elk departure from winter range involved a trade‐off between current and anticipated forage conditions, while snow melt governed summer range arrival date. Timing of elk departure from summer range and arrival on winter range were both influenced by snow accumulation and exposure to hunting. At the GYE scale, spring and fall migration timing changed through time, most notably with winter range arrival dates becoming almost 50 days later since 2001. Predicted herd‐level changes in migration timing largely agreed with observed GYE ‐wide changes—except for predicted winter range arrival dates which did not reflect the magnitude of change detected in the elk telemetry data. Snow melt, snow accumulation, and spring green‐up dates all changed through time, with different herds experiencing different rates and directions of change. We conclude that elk migration is plastic, is a direct response to environmental cues, and that these environmental cues are not changing in a consistent manner across the GYE . The impacts of changing elk migration timing on predator–prey dynamics, carnivore–livestock conflict, disease ecology, and harvest management across the GYE are likely to be significant and complex.

Brown bear (Ursus arctos) body size, condition, and productivity in the Arctic, 1977–2016 - Grant V. Hilderbrand; Kyle Joly; Mathew S. Sorum; Matthew D. Cameron; David D. Gustine (Polar Biology, 2019)

Plasticity in physiological condition of female brown bears across diverse ecosystems - Grant V. Hilderbrand; David D. Gustine; Buck Mangipane; Kyle Joly; William Leacock; Lindsey Mangipane; Joy Erlenbach; Mathew S. Sorum; Matthew D. Cameron; Jerrold L. Belant; Troy Cambier (Polar Biology, 2018)

Dietary plasticity in a nutrient-rich system does not influence brown bear (Ursus arctos) body condition or denning - Lindsey S. Mangipane; Jerrold L. Belant; Diana J. R. Lafferty; David D. Gustine; Tim L. Hiller; Michael E. Colvin; Buck A. Mangipane; Grant V. Hilderbrand (Polar Biology, 2018)